2016
DOI: 10.1108/ijwbr-03-2016-0009
|View full text |Cite
|
Sign up to set email alerts
|

Wine labels: an eye-tracking and pupillometry study

Abstract: Purpose The purpose of this paper was to investigate how attention to wine labels related to preference by using quantitative measures of gaze and of the diameter of the eye pupil. We assessed whether eye fixations could predict choices and willingness to pay and whether pupil size could index the aesthetic value of wine labels. More specific goals were to identify which elements of a wine label captured attention the most and to assess whether an authentic label would be preferred by naïve consumers over othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 77 publications
4
32
0
Order By: Relevance
“…Hence, we monitored eye fixations during a "beauty contest" task. In each trial, we showed side by side a pair of faces and requested participants to decide which of the two individuals looked more attractive, by pressing one of two keys, since previous eye-tracking studies of aesthetic decisions or consumers' preferences have shown a tight relation between gaze onto a particular item and preference [59][60][61]. Comparing oculomotor behavior could reveal sex differences in attending to female versus male faces [62], which again might turn out to be different for different SF bands.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, we monitored eye fixations during a "beauty contest" task. In each trial, we showed side by side a pair of faces and requested participants to decide which of the two individuals looked more attractive, by pressing one of two keys, since previous eye-tracking studies of aesthetic decisions or consumers' preferences have shown a tight relation between gaze onto a particular item and preference [59][60][61]. Comparing oculomotor behavior could reveal sex differences in attending to female versus male faces [62], which again might turn out to be different for different SF bands.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, even when having awards in the labelwhich serve as a proxy of product quality -producers must draw attention to the label. Here pictorial elements are crucial to increase attractiveness (Laeng, Suegami & Aminihajibashi, 2016). Such effectiveness is also relevant for retailers, who may add increased benefits to the brand by showing the wine in a specific environment rather than alone, with little or no context involving it.…”
Section: Resultsmentioning
confidence: 99%
“…These conclusions add fresh insights and different perspectives to the existing literature, in which there is evidence that products with higher saliency, in this case, wine labels with awards, attract more rapidly consumers' attention but do not retain it for long periods and the opposite is true for bottles without awards (Jaeger et al, 2018;Vuori et al, 2004), confirming the existence of negative relationship between perceived quality and attention. Regardless, the role of visual attention on purchase intention cannot be disregarded, since it plays a major role on influencing consumers' preferences, choices and purchase acts (Laeng et al, 2016;Pieters and Warlop, 1999;Shimojo et al, 2003), which is strengthen in the presence of awards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wine sector is overcrowded with brands, and differentiation is increasingly difficult (Bruwer, 2004;Johnson and Bruwer, 2007;Brochado et al, 2015). While the wine literature has examined the relationship between brand and geographical indication (Schamel, 2006;Durrieu, 2008;Teuber, 2011), packaging/label (Rundh, 2005;Boudreaux and Palmer, 2007;Laeng et al, 2016) and wine tourism (Lockshin and Spawton, 2001;Bruwer and Lesschaeve, 2012) in affecting brand perceptions offline, the wineries' online presence has mostly been ignored. Although some authors have highlighted a particular interest of wine literature in consumer behavior research studies (Lockshin and Corsi, 2012), the firm's perspective on this topic has not been sufficiently investigated.…”
Section: Introductionmentioning
confidence: 99%